Investigation of Cytotoxic Effects of Tragopogon reticulatus Against HepG2 and MCF-7 Cell Lines and Antioxidant, Antimicrobial Effects Against Some Microorganisms - Dalkilic, Lütfiye Kadioglu; Dalkilic, Semih (My University, 2024)
Plants have been used for various purposes throughout history. This subject has received increasing attention in the field of traditional medicine in recent years. Tragopogon reticulatus, as a forage grass plant in turkey, is a species that stands out with rich vitamin and mineral content. The aim of this study was to investigate the antimicrobial, antioxidant, and cytotoxic activities of T. reticulatus. Two separate extracts were prepared at different concentrations using hexane and methanol solvents obtained from the T. reticulatus plant, and cytotoxic activity was evaluated by the MTT Assay (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) method on human liver cancer (HepG2) and human breast cancer (MCF7) cell lines. The antioxidant activity of the extracts obtained from methanol and hexane was determined by the DPPH (2,2-diphenyl 1-picrylhydrazyl) radical scavenging capacity method. Antimicrobial activity was evaluated by the disk diffusion method, and bacteria such as Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli, Bacillus megaterium, and Candida albicans fungus were used in the study. The hexane extract obtained from the T. reticulatus plant showed a high cytotoxic activity of 44% in the MCF7 cell line, while it showed a 51% dead cell count in the HepG2 cell line. When the antioxidant results were evaluated, it was determined that the DPPH radical scavenging effect of the hexane extract exhibited the most effective activity at 19%. When the antimicrobial results were evaluated, it was determined that the concentrations prepared with hexane exhibited the most effective activity with a zone diameter of 16 mm against B. megaterium. These findings suggest that T. reticulatus plant extracts can be considered as a potential source. These results may shed light on future research into the biological effects of the plant and contribute to the development of new treatment methods.
Keywords: Antioxidant activity; Antimicrobial; Cytotoxic; Tragopogon reticulatus